A Comparative Study of the Reasons for the Persistence of Buddhism and the Decline of Zoroastrianism in Ancient China - Amin Yazdkhasti; Hamidreza Pashazanous (Comparative Theology)
The topic of religion in the history of relations between the two civilizations of Iran and China is an issue that has not been addressed much. According to Chinese sources and other documents, Buddhism and Zoroastrianism were introduced to China by Iranians. So far, some studies have been conducted on Buddhism and Zoroastrianism in China, but these works have only explained how these religions entered China, but the reasons for the persistence of Buddhism and the decline of Zoroastrianism from the middle of the 9th century onwards in China have not been considered. Therefore, the present study, relying on the library method and the comparative analysis of the historical data obtained from China, tries for the first time to address the reasons for the persistence of Buddhism and the decline of Zoroastrianism in ancient China. The claim of the authors is that Buddhism has survived until today due to its compatibility and assimilation with Chinese thought and society and not having a political approach, especially from the 9th century onwards; on the other hand, due to the heterogeneity of its teachings and religious rituals in China, the Zoroastrianism could not adapt to this land and the cultural characteristics of its people. Keywords: China, Buddhism, Zoroastrianism, Permanence, Decline. IntroductionDuring the Parthian and Sasanid periods, Iran influenced many Eastern cultures and was influenced by them in return. It is possible to understand this trend by examining the political, economic, and cultural relations between Iran and the Central Asian countries, along with China. One of the most important methods of exchanging cultural elements from Iran to China has been the transfer of various religions to this land. This process continued during the reign of Han (202 BC-220 AD) until the middle of Tang (618-907 AD). The arrival of Buddhism in China during the reign of the Han took place almost simultaneously with the rule of the Parthians (247 BC-224 AD) in Iran. During the Parthian period, Buddhism entered China through translators, aristocrats, and the Parthian elite class, and for the first time, a Parthian prince called An Shigao. Zoroastrianism entered China in the 6th century AD and during the Sassanid period. Despite the fact that in some regions of China, especially in the North of China, the influence of Zoroastrianism can be seen, this religion, which was mostly transmitted through cultural interactions, was not successful in China for various reasons. Materials and MethodsThe present study was conducted using the library method and comparative analysis of historical data obtained from China. Research FindingsVarious factors and contexts caused Buddhism to open its place among the Chinese people in China, despite the various obstacles it faced in the history of its presence in this land, and alongside the indigenous religions of Confucianism and Tao, as a religion to be known as important, popular and respected in this land. Even today, Buddhism is considered one of the most important and popular religions in China and compared to Zoroastrianism, which disappeared in China centuries ago, it has gained much more popularity in the Chinese society.The Zoroastrian religion could not gain much popularity among the Chinese people compared to the Buddhist religion. It seems that most of the followers of the Zoroastrian religion in China were non-Chinese. The main claim of this study is that Buddhism adopted a non-political approach, especially since 845 AD. Later, compared to Iranian religions and especially Zoroastrianism, it was not widely suppressed by the Tang government. Buddhism with its pacifist and conservative approach, institutionalized the principle of accepting the concept of suffering as a reality in the world and offered the Chinese people what they wanted and remained in this land. Discussion of Results and ConclusionsConsidering the results of the present study, the factors that caused the popularity and longevity of Buddhism in China can be summarized in four cases in order of importance: 1) Reign support, 2) Compatibility with local customs and traditions, 3) Mixing with Chinese religions, and 4) Effective propaganda and education.The approach of Buddhism, especially in the school of Mahayana, caused these values to have positive spiritual and social effects on the Chinese people and they viewed this religion as a solution to end the long-term political and social violence in their land. The comparative study of these factors showed that all of these issues are true in a negative way about the failure and decline of Zoroastrianism in China.